A Systematic Literature Review: the Role of Balanced Scorecard in Performance Measurement for Corporate Sustainability - Asri Usman; Mediaty; Nadhilah Amaliah Liwan; Oktavia Nindita (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to improve sustainable business performance through Balanced Scorecard (BSC) with a systematic literature review method from 2018 to 2022, using Watase Uake, which resulted in 28 selected articles. BSC has proven to be strategic in improving the holistic performance of companies, covering 4 main perspectives: financial, customer, development and growth, and internal process. The internal process perspective was more influential in strategizing to measure company performance, followed by the training and development perspective, and then the customer and financial perspectives. The four perspectives of performance measurement using the balanced scorecard are interrelated so that the internal process makes improvements in the learning and development perspective, which in turn leads to finance by bringing benefits to customer satisfaction.